A brief review of plant diseases caused by Cactus virus X. (May 2021) - Evallo, Edzel; Taguiam, John Darby; Balendres, Mark Angelo
Abstract: Plant pathogens, including viruses, have a known negative impact on plant growth and development. Here, plant diseases caused by cactus virus X (CVX) are reviewed. CVX infects a range of plant species within the Cactaceae family. When expressed, symptoms include chlorosis, necrosis, and morphological alterations, such as the twisting of arms, but at times plants can be asymptomatic. CVX may be transmitted through contaminated grafting or cutting tools and can also occur as mixed infections with other viruses, including zygocactus virus X and pitaya virus X . CVX may also play a role in altering the plant's physiology. The virus can be detected by molecular assays, including polymerase chain reaction (PCR), and transmitted to indicator plants. Sanitation in both nurseries and fields is critical in controlling the spread of CVX. This paper highlights CVX as a potential production threat to some Cactaceae family members, particularly the now popular Hylocereus species or dragon fruits. Highlights: Cactus virus X (CVX) infects many cacti plants. Disease symptoms include mottling, chlorosis, and necrosis, but some plants may appear asymptomatic. CVX can be detected using molecular assays. CVX spread is prevented by proper field sanitation and removal of infected planting materials.